PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP PRAKTIK FRAUDULENT ACTIVITIES DI PASAR MODAL DAN IMPLEMENTASI SANKSI BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1995 TENTANG PASAR MODAL (Studi Kasus PT. Garuda Indonesia Tbk) - Hasni, Nadia Nuraini; Astawa, I Ketut; Nurlailasari, Ella (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
The capital market plays an important role as a means for companies to raise funds and for individuals to invest, but it is vulnerable to various fraudulent practices, such as financial statement manipulation. One significant case is the manipulation of PT. Garuda Indonesia Tbk’s financial statements in 2018, where the company falsely recognized USD 239.94 million in revenue, creating an illusion of profit and harming investors. This study aims to analyze legal protection for investors against fraudulent activities in the capital market and evaluate the relevance of sanctions imposed by the Financial Services Authority (OJK) based on Law Number 8 of 1995 concerning the Capital Market. Using a normative juridical method and a descriptive-analytical approach, the study examines the inconsistency between administrative sanctions imposed and the criminal provisions stipulated in the law. The findings reveal that administrative sanctions such as fines and orders to restate financial statements imposed by OJK fail to provide a deterrent effect and are disproportionate to the harm caused to investors and the integrity of the capital market. Instead, such financial statement manipulation should be classified as a crime under Article 107 of Law Number 8 of 1995, which prescribes criminal penalties such as imprisonment and fines for perpetrators. Furthermore, this study highlights the crucial role of OJK in strengthening supervision and enforcing stricter sanctions to enhance legal protection for investors and maintain public trust in the capital market. Accordingly, the study recommends policy revisions to ensure sanctions are better aligned with the severity of violations and emphasizes the need for improved transparency and accountability of issuers to prevent future manipulation practices